PENURUNAN REJECT SPRAY DUST PADA JORAN PANCING DENGAN METODE PDCA UNTUK MENINGKATKAN KUALITAS PRODUCT DI PT SHIMANO BATAM - Sumarya, Edi; Ramadhoni, Rendy; Methalina Afma, Vera (University of Riau Kepulauan, 2023)
The quality control process implements continuous improvements using the Plan Do Check Action (PDCA) method. It uses seven tools where quality control is carried out from the initial production process, ongoing production, and up to finished production. Even though the quality control process has been carried out, the quality of the product is still poor, especially in the area of line spray painting. Data per July-September 2023 recorded 873 defective units with the most dominant spray dust defects with 543 defective units. Using the PDCA method aims to map all the problems above, the purpose of this study is to find out the causes of the most dominant reject spray dust and to find out the factors and determine solutions to reduce spray dust rejection. The PDCA method is used to make improvements that are known. several factors cause spray dust rejection due to the lack of routine maintenance procedures resulting in the performance of the spray gun not being maximized, not cleaning the gun spray every time the process changes which causes the rest of the spray to clog, paint that has expired causing the quality of the paint not to be optimal, lack of control over room temperature and the place for sterilization to enter the spray room is a factor for the large number of rejected spray dust. October-December 2023 recorded a decrease in reject spray dust units from 543 units to 243 units reject.